'Friends and grades': Peer preference and attachment predict academic success among Naskapi youth. (August 2013) - Burack, Jacob A.; D'Arrisso, Alexandra; Ponizovsky, Vladimir; Troop-Gordon, Wendy; Mandour, Tarek; Tootoosis, Curtis; Robinson, Sandy; Iarocci, Grace; Fryberg, Stephanie
The primary findings of this study are preliminary support for the promotive effects of positive peer relations in an educational context with a specific group of First Nations adolescents. Eighty-one students from grades 6–11 who attended the sole school in the Naskapi community of Kawawachikamach in northern Québec, representing virtually all of the youths in the community, completed questionnaires regarding peer preferences, self-report peer and parental attachment, and affiliation with mainstream White and Native culture. Based on a regression analysis with full information maximum likelihood (FIML) analyses to handle missing data, only the measures of peer preference and self-report attachment to peers were found to predict school grades. These findings are inconsistent with the oppositional hypothesis that has been forwarded with other minority youths from historically oppressed communities, but rather are evidence for the beneficial effects of 'peer power' in this community.